Experience of emergency department patients after a visit for hyperglycaemia: implications for communication and factors affecting adherence postdischarge. Issue 2 (4th May 2021) - Yan, Justin; Azzam, Dimah; Columbus, Melanie; Van Aarsen, Kristine; Liu, Selina; Spaic, Tamara; Shepherd, Lisa
Abstract : Background: While studies have reported factors affecting adherence to diabetic care plans from a chronic disease perspective, no studies have addressed issues with post-discharge adherence facing patients with diabetes after an emergency department (ED) presentation for hyperglycaemia. This study's objectives were to describe patient perspectives on their experience during and after an ED visit for hyperglycaemia and to identify factors that influence postdischarge adherence. Methods: We conducted a qualitative description (QD) study of adult patients who had visited a Canadian ED for hyperglycaemia. Consistent with QD, purposive sampling was utilised, seeking diversity across age, gender and diabetes type. Participants took part in semistructured interviews and thematic analysis was used to identify and describe core themes. Frequent team meetings were held to review the analysis and to develop the final list of themes used to recode the data set. Analytic insights were tracked using reflective memos and an audit trail documented all steps and decisions. Results: 22 patients with type 1 and 2 diabetes were interviewed from June to October 2019. Participants identified several factors that impacted their ability to adhere to discharge plans: communication of instructions, psychosocial factors (financial considerations, shame and guilt, stigma and mental health), access to follow-up care and paediatric to adult care transitions. Conclusions: This study describes the patient experience with the communication of discharge instructions, as well as factors affecting adherence post-ED discharge for hyperglycaemia. Our findings suggest four strategies that could improve the patient experience, improve adherence to discharge plans and potentially decrease the frequency of recurrent ED visits for hyperglycaemia.